Workaway : the human costs of Europe's common labour market - Moses, Jonathon Wayne, 1962- (Bristol University Press, 2021)
This agenda-setting book argues that the process of market integration in Europe has undermined the power and influence of European workers and generated significant human costs. In starting from the position of labour, this book offers an alternative approach which balances the needs of justice and efficiency.